Analisis Pengaruh Penggunaan Aluminium Foil Pada Dinding Mesin Penetas Telur Terhadap Daya Tetas Yang Dihasilkan - Agusti, Tri; Gunawan, Yuspian; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2021)
The hatching machine is one of the media in the form of a box with such a construction that the heat inside is not wasted. This incubator is equipped with supporting equipment to regulate environmental conditions similar to or similar to the broodstock. The purpose of this study is to determine the effect of the use of a layer of aluminum foil on the walls of the egg incubator on the resulting hatchability. This research was conducted by installing an incubator, then testing it using an incubator. Data were collected by measuring room temperature, room humidity, light on and off, and checking embryo development. The results showed that the egg incubator without aluminum foil layer began to hatch on the 20th day as many as 3 eggs, and on the 21st day as many as 4 eggs so that the eggs hatched were 7 out of 10 eggs and for the egg incubator with a layer aluminum foil hatched early on the 19th day as many as 2 eggs, on the 20th day as many as 3 eggs and on the 21st day as many as 4 eggs so that the eggs hatched were 9 eggs out of 10 eggs. The use of aluminum foil in the egg incubator affects the hatchability.Keywords: Egg incubator, aluminum foil coating, hatchability.